Acrylic soft resin composition for denture bases
By using a monofunctional polymerizable monomer in the acrylic soft resin composition for denture beds, the issues of flexibility loss and durability in acrylic soft lining materials are addressed, resulting in a composition that maintains long-term compatibility and reduces pain by evenly distributing pressure.
Patent Information
- Application Number
- JP2024164735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-08
AI Technical Summary
Acrylic soft lining materials used in denture beds lose flexibility over time due to the elution of plasticizers, leading to reduced durability and compatibility with the oral mucosa.
Incorporating a monofunctional polymerizable monomer with a specific structure into the acrylic soft resin composition, which reduces the need for high plasticizer content and maintains flexibility even in wet oral environments.
The solution provides an acrylic-based soft resin composition for denture beds with improved durability and flexibility, ensuring long-term compatibility with the oral mucosa and reducing pain by evenly distributing pressure.
Smart Images

Figure 2025056768000001 
Figure 2025056768000002 
Figure 2025056768000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic soft resin composition for denture bases, which is used in dental treatment to compensate for the lost viscoelasticity of the alveolar ridge mucosa by lining the mucosal surface of the denture base with a soft material similar to the mucosa, thereby mitigating the impact during biting with its cushioning effect and improving or eliminating pain by distributing pressure evenly over the entire alveolar ridge. [Background technology]
[0002] In dental treatment, dentures are worn by patients who have lost teeth due to caries, periodontal disease, fractures, etc., to restore oral function and aesthetics. However, if the dentures are worn for a long period of time and bone resorption progresses due to some factor, the covering mucosa becomes thin, and the mucosa under the denture base cannot relieve the occlusal pressure, so that the occlusal force is directly transmitted to the jawbone, and the burden on the alveolar ridge increases. Therefore, the thin mucosa sandwiched between the hard denture base and the inelastic alveolar bone causes pain and damage every time the patient bites. In addition, since resorption is also observed in the alveolar ridge with age, even if a denture is worn well, the denture will become non-fitting over time. When treatment for these problems becomes necessary, a hardening composition called a lining material is used to replace one layer of the mucosal surface of the denture base. There are hard lining materials and soft lining materials, and each is used depending on the case. In an ultra-aged society where the aging of the population is progressing rapidly, there has been a rapid increase in difficult cases, such as cases where the alveolar ridge has been absorbed to the point of appearing as a boat bottom, or where the mucosa under the denture base has become so thin that pain cannot be avoided, and soft lining materials are useful for such difficult cases. In other words, soft lining materials compensate for the lost viscoelasticity of the alveolar ridge mucosa, and their cushioning effect can reduce the impact of biting and distribute pressure evenly over the entire alveolar ridge.
[0003] Currently, acrylic soft lining materials (Patent Document 1, Patent Document 2) and silicone soft lining materials (Patent Document 3) are mainly used as soft lining materials. Of these, acrylic soft lining materials have viscoelasticity similar to that of the alveolar ridge mucosa, and therefore have material properties closer to those of the living body than silicone soft lining materials, which are elastic. In addition, acrylic soft lining materials have the advantages of being repairable and not easily peeled off from the denture base (Non-Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2002-104913 A [Patent Document 2] JP 2002-119523 A [Patent Document 3] JP 2002-60311 A [Non-patent literature]
[0005] [Non-Patent Document 1] Kazuhiko Mushimoto et al., Quintessence of Dental Technology, Vol. 28 / 2003, 801-818 Summary of the Invention [Problem to be solved by the invention]
[0006] It has been pointed out that the flexibility of acrylic soft lining materials is achieved by blending a large amount of plasticizer, and the plasticizer gradually dissolves in the oral cavity, causing the flexibility to be lost over time. In other words, compared with silicone soft lining materials that do not contain dissolving components after curing, acrylic soft lining materials have inferior durability in the oral cavity. Therefore, the present invention aims to provide an acrylic soft resin that can maintain flexibility in the oral cavity for a long period of time and has excellent durability. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the inventors have discovered that by using a monofunctional polymerizable monomer having a specific structure represented by the following general formula (1) in an acrylic soft resin, it is possible to exhibit excellent flexibility suitable for a soft resin even when the amount of plasticizer blended is reduced, and in addition, the flexibility is maintained for a long period of time even in an oral cavity environment that is constantly moist and subject to stress due to occlusion, and have completed the present invention.
[0008] That is, the acrylic soft resin composition for denture base of the present invention is composed of a liquid material containing a monofunctional polymerizable monomer represented by the following general formula (1) and a powder material containing organic polymer particles that can be swelled or dissolved by the liquid material, and is characterized in that at least one of the liquid material and the powder material contains a polymerization initiator. [ka] (In the formula, R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched divalent hydrocarbon group having 1 to 10 carbon atoms which may contain an ether bond; X 1 represents -O- or -NH-.) Effect of the Invention
[0009] According to the present invention, it is possible to provide an acrylic soft resin composition for denture base which is excellent in flexibility and inhibits deterioration of the flexibility over time. By lining the mucosal surface of a denture with the acrylic soft resin composition for denture base of the present invention, it is possible to protect the oral mucosal surface with which the denture base comes into contact for a long period of time, and also to maintain the compatibility of the denture with the oral mucosal surface for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The acrylic soft resin composition for denture base of the present invention will be described in detail below.
[0011] In this specification, (meth)acrylate refers to both acrylate and methacrylate, (meth)acryloyl refers to both acryloyl and methacryloyl, (meth)acrylic acid refers to both acrylic acid and methacrylic acid, and (meth)acrylamide refers to both acrylamide and methacrylamide.
[0012] In this specification, the degree of flexibility of the soft resin is indicated by the "Durometer A hardness after 24 hours and after 30 days" as an index. The test method is in accordance with "JIS T 6520:2019 Long-term elastic lining material for denture base."
[0013] The acrylic soft resin composition for denture base of the present invention is composed of a liquid material containing a monofunctional polymerizable monomer of a specific structure represented by the general formula (1) described later, and a powder material containing organic polymer particles that can be swelled or dissolved by the liquid material, and at least one of the liquid material and the powder material contains a polymerization initiator. The acrylic soft resin composition for denture base of the present invention starts to harden by mixing an appropriate amount of the liquid material and the powder material, and the hardened product exhibits excellent flexibility. Furthermore, the acrylic soft resin composition for denture base of the present invention has a lower plasticizer content than conventional acrylic soft resin compositions for denture base, and the hardened product has less unreacted components remaining. As a result, the acrylic soft resin composition for denture base of the present invention maintains its flexibility for a long period of time after hardening because there is almost no elution of components in the oral cavity in a moist environment.
[0014] First, various components to be blended in the liquid material of the acrylic soft resin composition for denture base of the present invention will be described.
[0015] The liquid material of the acrylic soft resin composition for denture base of the present invention contains, as an essential component, a monofunctional polymerizable monomer represented by the following general formula (1). The monofunctional polymerizable monomer plays a role in imparting flexibility to the cured product of the acrylic soft resin composition for denture base of the present invention. [ka] (In the formula, R1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched divalent hydrocarbon group having 1 to 10 carbon atoms which may contain an ether bond; X 1 represents -O- or -NH-.)
[0016] Specific examples of the monofunctional polymerizable monomer represented by the general formula (1) include o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate, 2-(p-phenoxyphenyl)ethyl (meth)acrylate, 3-(o-phenoxyphenyl)propyl (meth)acrylate, 3-(m-phenoxyphenyl)propyl (meth)acrylate, 3-(p-phenoxyphenyl)propyl (meth)acrylate, 4-(o-phenoxyphenyl)propyl (meth)acrylate, 4-(p ... Examples of the acrylates include, but are not limited to, 4-(m-phenoxyphenyl)butyl (meth)acrylate, 4-(p-phenoxyphenyl)butyl (meth)acrylate, 5-(o-phenoxyphenyl)pentyl (meth)acrylate, 5-(m-phenoxyphenyl)pentyl (meth)acrylate, 5-(p-phenoxyphenyl)pentyl (meth)acrylate, 6-(o-phenoxyphenyl)hexyl (meth)acrylate, 6-(m-phenoxyphenyl)hexyl (meth)acrylate, and 6-(p-phenoxyphenyl)hexyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, because they easily swell or dissolve organic polymer particles, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate, and 2-(p-phenoxyphenyl)ethyl (meth)acrylate are more preferred, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, and p-phenoxybenzyl (meth)acrylate are even more preferred, and m-phenoxybenzyl acrylate is the most preferred.
[0017] The content of the monofunctional polymerizable monomer represented by the general formula (1) in the acrylic soft resin composition for denture base of the present invention is preferably in the range of 0.5% by mass to 70.0% by mass, more preferably 5.0% by mass to 50.0% by mass, and even more preferably 10.0% by mass to 30.0% by mass. If the content of the monofunctional polymerizable monomer represented by the general formula (1) is less than 0.5% by mass, the cured product may become hard and lack flexibility. If the content exceeds 70.0% by mass, the amount of unpolymerized polymerizable monomer increases, and the surface of the cured product may become sticky.
[0018] The liquid material of the acrylic soft resin composition for denture base of the present invention may optionally contain polymerizable monomers other than the monofunctional polymerizable monomer represented by the general formula (1) (hereinafter referred to as "other polymerizable monomers") in order to adjust compatibility with the powder material, swelling speed, working time, curing time, flexibility of the cured product, etc., or to improve durability of the cured product.
[0019] The other polymerizable monomer is not particularly limited in its molecular structure, and a known polymerizable monomer can be used. That is, examples of the polymerizable unsaturated group possessed by the other polymerizable monomer include, but are not limited to, a (meth)acryloyloxy group, a (meth)acrylamide group, a styryl group, a vinyl group, an allyl group, and the like. Among these polymerizable unsaturated groups, a (meth)acryloyloxy group or a (meth)acrylamide group is preferable because of its excellent polymerization rate, and a (meth)acryloyloxy group is more preferable. In addition, the number of polymerizable unsaturated groups possessed by the other polymerizable monomer is also not particularly limited. The hydrocarbon group bonded to the other polymerizable unsaturated group may be any of an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a combination thereof, and the hydrocarbon group may have any substituent such as an acidic group, a hydroxyl group, a halogen atom, a sulfur atom, an alkoxy group, an amino group, and a glycidyl group. Specific examples of the other polymerizable monomer are given below.
[0020] Other monofunctional polymerizable monomers include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, t) acrylate, stearyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, cyclohexyl (meth) acrylate, adamantyl (meth) acrylate, phenyl (meth) acrylate, phenoxydiethylene glycol (meth) acrylate, methoxypolyethylene glycol (meth) acrylate, benzyl (meth) acrylate, 2-phenylethyl (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, glycidyl (meth) acrylate, isobornyl ( (meth)acrylate, allyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, (meth)acryloyloxyethyl methyl succinate, 2-(meth)acryloyloxyethyl (Meth)acrylic acid esters such as acetoacetoxyethyl (meth)acrylate, acetoacetoxypropyl (meth)acrylate, and acetoacetoxybutyl (meth)acrylate; silane compounds such as γ-(meth)acryloyloxypropyltrimethoxysilane and γ-(meth)acryloyloxypropyltriethoxysilane; amines such as 2-(N,N-dimethylamino)ethyl (meth)acrylate and 2-(N,N-diethylamino)ethyl (meth)acrylate; 2,2,Examples of the fluorine-containing (meth)acrylates include 2-trifluoroethyl (meth)acrylate, perfluorohexylethyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, and their (meth)acrylamides, as well as N-methylol (meth)acrylamide.
[0021] Examples of aromatic bifunctional polymerizable monomers include 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxyethoxyphenyl)- ... 2-(4-(meth)acryloyloxydiethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, and (meth)acrylamides thereof.
[0022] Examples of the aliphatic bifunctional polymerizable monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9- Examples of such acrylates include nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, glycerol-1,3-dimethacrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)ethane, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, 2-hydroxy-1,3-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, and (meth)acrylamides thereof.
[0023] Examples of the trifunctional or higher polymerizable monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and (meth)acrylamides thereof.
[0024] Examples of the urethane-based polymerizable monomer include (meth)acrylate compounds having a urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, or 3-chloro-2-hydroxypropyl (meth)acrylate, with an isocyanate compound, such as methylcyclohexane diisocyanate, methylene bis(4-cyclohexyl isocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methylmethylbenzene, or 4,4-diphenylmethane diisocyanate.
[0025] In addition to the above polymerizable monomers, oligomers or polymers having at least one polymerizable group may be used. The above other polymerizable monomers are not limited to these, and may be used alone or in combination.
[0026] Among the other polymerizable monomers contained in the acrylic soft resin composition for denture base of the present invention, the content of the monofunctional polymerizable monomer is preferably in the range of 0.5% by mass to 45.0% by mass, more preferably in the range of 5.0% by mass to 40.0% by mass, based on the total composition. If the content of the monofunctional polymerizable monomer is less than 0.5% by mass, the intended adjustment or improvement effect may not be sufficiently obtained with respect to compatibility with powder materials, swelling speed, operation time, curing time, flexibility and durability of the cured product, etc. Also, if it exceeds 45.0% by mass, the flexibility of the cured product may be lost.
[0027] In addition, among the other polymerizable monomers contained in the acrylic soft resin composition for denture base of the present invention, the content of the difunctional or higher polymerizable monomer is preferably in the range of 0.05% by mass to 20.0% by mass, more preferably in the range of 0.5% by mass to 3.0% by mass, based on the entire composition. If the content of the difunctional or higher polymerizable monomer is less than 0.05% by mass, the flexibility of the cured product may be lost when exposed to the oral cavity environment for a long period of time. If the content exceeds 20.0% by mass, the flexibility of the cured product may be lost.
[0028] A plasticizer may be optionally blended into the liquid material of the acrylic soft resin composition for denture base of the present invention in order to adjust the flexibility of the cured product, compatibility with powder materials, swelling speed, handling time, curing time, etc.
[0029] The plasticizer that can be used in the acrylic soft resin composition for denture base of the present invention is not particularly limited, and known plasticizers can be used without any restrictions. Specific examples of plasticizers include phthalates such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diheptyl phthalate, bis(2-ethylhexyl) phthalate, dioctyl phthalate, diisodecyl phthalate, butyl benzyl phthalate, diisononyl phthalate, ethyl phthalyl ethyl glycolate, and butyl phthalyl butyl glycolate, dibutyl adipate, diisobutyl adipate, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, dibutyl diglycol adipate, dibutyl sebacate, bis(2-ethylhexyl) sebacate, dioctyl sebacate, Examples of the plasticizer include, but are not limited to, dibasic acid esters other than phthalic acid, such as dibutyl maleate, bis(2-ethylhexyl) maleate, dibutyl fumarate, and diethyl succinate, trimellitic acid esters, such as tris(2-ethylhexyl) trimellitate, glycerin esters, such as glycerol triacetate, phosphoric acid esters, such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, tris(2-ethylhexyl) phosphate, trioctyl phosphate, and triphenyl phosphate, and carboxylic acid esters, such as benzyl benzoate, ethyl benzoate, butyl benzoate, and amyl benzoate. These plasticizers may be used alone or in combination.
[0030] The content of the plasticizer in the acrylic soft resin composition for denture base of the present invention is 30.0% based on the entire composition. It is preferable that the content of the plasticizer is in the range of 0.5% by mass or less, more preferably 17.0% by mass or less, even more preferably 2.5% by mass or less, and most preferably substantially free of plasticizer. In this specification, "substantially free of plasticizer" means that the plasticizer is not intentionally blended into the composition, and the plasticizer is included in the composition as a trace amount of impurity or additive in other components, and is mixed into the composition. However, even if the plasticizer is mixed in unintentionally, the content of the plasticizer needs to be 0.5% by mass or less with respect to the entire composition. If the content of the plasticizer exceeds 30.0% by mass, the plasticizer will gradually dissolve in the oral cavity environment, and the flexibility of the cured product may be lost over time, or dimensional changes may occur.
[0031] The monofunctional polymerizable monomer represented by the general formula (1), other polymerizable monomers, and plasticizers which can be blended into the liquid material of the acrylic soft resin composition for denture base of the present invention described above can be blended into the powder material described below without any problem, so long as they are in a small amount that does not adversely affect the operability or various properties of the acrylic soft resin composition for denture base of the present invention.
[0032] The liquid material of the acrylic soft resin composition for denture base of the present invention can optionally contain an organic solvent in order to lower the viscosity and improve the initial compatibility when mixing with the powder material begins, and also to facilitate penetration into the powder material and increase the swelling rate.
[0033] Specific examples of organic solvents that can be included in the liquid material of the present invention include, but are not limited to, alcohols such as methanol, ethanol, isopropyl alcohol, and isobutyl alcohol, ketones such as methyl ethyl ketone and acetone, and alkyl halides such as dichloromethane, chloroform, and carbon tetrachloride. These organic solvents can be used alone or in combination. Among these organic solvents, ethanol, isopropyl alcohol, butyl alcohol, acetone, and the like are preferably used from the viewpoint of safety.
[0034] The content of the organic solvent in the liquid material of the acrylic soft resin composition for denture base of the present invention is preferably in the range of 0.1% by mass to 10.0% by mass, more preferably in the range of 0.1% by mass to 5.0% by mass. If the content of the organic solvent is less than 0.1% by mass, sufficient improvement effects may not be obtained in terms of initial compatibility at the start of mixing with the powder material, permeability to the powder material, swelling speed, etc. On the other hand, if the content of the organic solvent exceeds 10.0% by mass, the organic solvent gradually dissolves in the oral cavity environment, and the flexibility of the cured product may be lost over time, causing dimensional changes.
[0035] Next, various components to be blended in the powder material of the acrylic soft resin composition for denture base of the present invention will be described.
[0036] The powder material of the acrylic soft resin composition for denture base of the present invention contains organic polymer particles that can be swelled or dissolved by a liquid material containing a polymerizable monomer as an essential component. The organic polymer particles become paste-like when mixed with the liquid material, making it easier to apply the mixture when applying it to a denture base and making it easier to ensure the thickness of the resin layer. In addition, it has the effect of reducing polymerization shrinkage during hardening. In this specification, "swellable or soluble" means that when 2 g of organic polymer particles and 1 g of liquid material are mixed for 15 seconds in an environment of 23°C, the particles are observed to swell or dissolve in the liquid material within 10 minutes from the start of mixing.
[0037] The organic polymer particles are not particularly limited in terms of their component composition, and can be made of various polymers, as long as they can be swollen or dissolved by a liquid material containing a polymerizable monomer. More specifically, the particles of the homopolymer of the monofunctional polymerizable monomer having the above-mentioned (meth)acryloyloxy group or (meth)acrylamide group, etc., the particles of the copolymer combining two or more types of monofunctional polymerizable monomers, and the particles of the copolymer combining the monofunctional polymerizable monomer having the (meth)acryloyloxy group and / or the (meth)acrylamide group with the polymerizable monomer not having the (meth)acryloyloxy group and the (meth)acrylamide group, such as styrene, α-methylstyrene, isoprene, butadiene, isobutylene, vinyl acetate, vinyl chloride, vinyl alcohol, ethylene, propylene, maleic acid, itaconic acid, and maleic anhydride, can also be used without any restrictions. Furthermore, there is no problem in using particles of a homopolymer of the above polymerizable monomer having no (meth)acryloyloxy group or no (meth)acrylamide group, or particles of a copolymer of two or more kinds of the above polymerizable monomers. The copolymer particles may be any copolymer such as a random copolymer, an alternating copolymer, or a block copolymer.
[0038] Among these organic polymer particles, from the viewpoint of the affinity of the acrylic soft resin composition for denture base of the present invention with the liquid material, it is preferable to use particles of a homopolymer of a monofunctional polymerizable monomer having a (meth)acryloyloxy group, or particles of a copolymer combining two or more kinds. Specific examples of these organic polymer particles include particles of homopolymers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc., and particles of a copolymer combining two or more kinds, but are not limited thereto. In addition, the organic polymer particles can be used without any restrictions even if they are partially crosslinked with the above-mentioned bifunctional or higher functional polymerizable monomer, as long as the amount is small enough that an extreme decrease in the swelling rate when the liquid material comes into contact with the organic polymer particles is not observed. These organic polymer particles can be used not only alone, but also in combination of a plurality of them.
[0039] There is no particular limitation on the polymerization method for producing these organic polymer particles, and they may be produced by any polymerization method such as emulsion polymerization, suspension polymerization, etc. Furthermore, the shape of these organic polymer particles may be any shape such as spherical, crushed, hollow, etc., but is preferably spherical in consideration of the flowability of the powder material.
[0040] The 50% particle size of the organic polymer particles is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm. If the 50% particle size of the organic polymer particles exceeds 150 μm, the swelling rate and curing time may be significantly slowed, which may adversely affect operability or cause roughness on the surface of the cured product. If the 50% particle size of the organic polymer particles is smaller than 10 μm, the swelling rate and curing time may be significantly faster (faster), which may adversely affect operability. Here, the "50% particle size" refers to the particle size when the cumulative value from the small particle size side is 50% in the volume-based particle size distribution measured using a laser diffraction / scattering type particle size distribution measuring device or the like.
[0041] The weight average molecular weight of the organic polymer particles is preferably in the range of 50,000 to 2,000,000, more preferably 100,000 to 1,200,000, and even more preferably 200,000 to 1,000,000. Here, the weight average molecular weight is the average molecular weight calculated based on the molecular weight distribution measured by gel permeation chromatography. When the weight average molecular weight of the organic polymer particles is less than 50,000, the swelling speed and curing time become significantly faster, which may have a negative effect on operability. When the weight average molecular weight of the organic polymer particles is more than 2,000,000, the swelling speed and curing time become significantly slower, which may have a negative effect on operability, such as a decrease in operability, and a brittle cured product.
[0042] The content of the organic polymer particles in the acrylic soft resin composition for denture base of the present invention is preferably in the range of 25.0% by mass to 70.0% by mass, more preferably 35.0% by mass to 65.0% by mass, and even more preferably 40.0% by mass to 60.0% by mass. If the content of the organic polymer particles is less than 25.0% by mass, the curing may be slowed down, the working efficiency may decrease, the amount of unpolymerized polymerizable monomer may increase, the surface of the cured product may become sticky, and the polymerization shrinkage may become large. On the other hand, if the content of the organic polymer particles exceeds 70.0% by mass, the cured product may become hard and lack flexibility.
[0043] In order to adjust the flexibility of the cured product, the powder material of the acrylic soft resin composition for denture base of the present invention can contain any rubber particles or elastomer particles that do not swell or dissolve in the liquid material containing a polymerizable monomer. In this specification, "does not swell or dissolve" means that when 2 g of organic polymer particles and 1 g of liquid material are mixed for 15 seconds in an environment of 23°C, the particles are not observed to swell or dissolve in the liquid material within 10 minutes from the start of mixing.
[0044] Specific examples of rubber particles include particles of natural rubber, synthetic rubber (synthetic isoprene rubber), butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, ethylene-propylene rubber, urethane rubber, silicone rubber, fluororubber, acrylic rubber, chlorosulfonated polyethylene rubber, epichlorohydrin rubber, polysulfide rubber, and the like, but are not limited to these.
[0045] Specific examples of elastomer particles include particles of polystyrene-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, ethylene-vinyl acetate copolymers, etc., but are not limited to these.
[0046] These rubber particles and elastomer particles can be used alone or in combination. The particle size, shape, and molecular weight of these rubber particles and elastomer particles can be appropriately selected or adjusted within a range that does not adversely affect the operability and properties of the acrylic soft resin composition for denture base of the present invention.
[0047] The amount of rubber particles and / or elastomer particles in the acrylic soft resin composition for denture base of the present invention is preferably in the range of 0.1% by mass to 5.0% by mass, more preferably in the range of 0.5% by mass to 3.0% by mass, based on the total amount of the composition. If the amount of rubber particles and / or elastomer particles is less than 0.1% by mass, the effect of imparting flexibility is poor, and if it exceeds 5.0% by mass, the compatibility of the powder material and the liquid material decreases, which may adversely affect operability.
[0048] The liquid and / or powder material of the acrylic soft resin composition for denture base of the present invention contains a polymerization initiator as an essential component. The polymerization initiator plays a role in initiating the polymerization reaction of the various polymerizable monomers.
[0049] The polymerization initiator that can be used in the acrylic soft resin composition for denture base of the present invention is not particularly limited, and any known polymerization initiator used in the dental field can be used without any restrictions. The polymerization initiators include those that initiate radical polymerization by the action of a compound of two or more components, such as redox initiators (sometimes called "chemical polymerization initiators" in the dental field. Hereinafter, they will be referred to as "chemical polymerization initiators"), those that initiate radical polymerization by heating (thermal polymerization initiators), and those that initiate radical polymerization by light irradiation (photopolymerization initiators). In the present invention, any polymerization initiator can be used without any restrictions. The polymerization initiator may be mixed into both the powder material and the liquid material, or into either the powder material or the liquid material, as long as it can sufficiently harden the polymerizable monomer.
[0050] Examples of the chemical polymerization initiator include, but are not limited to, organic peroxide / amine compound, organic peroxide / amine compound / aromatic sulfinic acid or its salt, or aromatic sulfonyl compound, organic peroxide / amine compound / (thio)barbituric acid compound or (thio)barbiturate compound, organic peroxide / amine compound / borate compound, organic peroxide / ascorbic acid compound, organic peroxide / thiourea / vanadium compound or copper compound, (thio)barbituric acid compound / organometallic compound / organohalogen compound, aromatic sulfinate salts that initiate radical polymerization by the action of an acidic compound, borate compounds, or (thio)barbiturate salts that initiate radical polymerization with an acidic compound, and organic boron compounds that initiate radical polymerization by reacting with oxygen or water.
[0051] Examples of the organic peroxide include diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, monoperoxycarbonates, peroxyketals, dialkyl peroxides, hydroperoxides, and ketone peroxides. More specific examples of the peroxide include benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, diacetyl peroxide, lauroyl peroxide, di-t-butyl peroxide, dicumyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-amyl hydroperoxide, isopropylbenzene hydroperoxide, 5-phenyl-4-pentenyl hydroperoxide, t-butylperoxyisopropyl carbonate, methyl ethyl ketone peroxide, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and t-butyl peroxybenzoate, but are not limited thereto.
[0052] The amine compound is preferably an aromatic secondary or aromatic tertiary amine, and specific examples thereof include N-methyl-p-toluidine, N-ethyl-p-toluidine, N-(2-hydroxyethyl)-p-toluidine, ethyl p-methylaminobenzoate, N-methylaniline, N-ethylaniline, N-(2-hydroxyethyl)aniline, N,N-dimethylaniline, N,N-diethylaniline, N,N-bis(2-hydroxyethyl)aniline, N-(2-hydroxyethyl)-N-methylaniline, N-ethyl-N-(2-hydroxyethyl)aniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl p-dimethylaminobenzoate, and the like, but are not limited thereto. Among these aromatic amine compounds, it is preferable to use N,N-dimethyl-p-toluidine or N,N-bis(2-hydroxyethyl)-p-toluidine from the viewpoint of reactivity with organic peroxides.
[0053] Examples of aromatic sulfinic acids or salts thereof, or aromatic sulfonyl compounds include benzenesulfinic acid, p-toluenesulfinic acid, o-toluenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and sodium salts, potassium salts, lithium salts, or ammonium salts thereof, or benzenesulfonyl chloride, benzenesulfonyl fluoride, benzenesulfonamide, benzenesulfonyl hydrazide, p-toluenesulfonyl chloride, p-toluenesulfonyl fluoride, p-toluenesulfonamide, p-toluenesulfonyl hydrazide, and the like, but are not limited thereto.
[0054] Examples of (thio)barbituric acid compounds or (thio)barbiturate compounds include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 5-laurylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, and the like. Examples of barbituric acid include, but are not limited to, sylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-phenyl-5-benzylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, thiobarbituric acid, 1,3-dimethylthiobarbituric acid, 5-phenylthiobarbituric acid, and their alkali metal salts (lithium, sodium, potassium salts, etc.), alkaline earth metal salts (calcium, strontium, barium salts, etc.), ammonium salts, tetramethylammonium salts, and tetraethylammonium salts.
[0055] Examples of borate compounds include trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(p-butyloxyphenyl) boron, monoalkyltriphenyl boron, monoalkyltris(p-chlorophenyl) boron, monoalkyltris(p-fluorophenyl) boron, monoalkyltris(p-butylphenyl) boron, monoalkyltris(p-butyloxyphenyl) boron, tetraphenyl boron, and tetrakis Examples of the salt include, but are not limited to, sodium salts, potassium salts, lithium salts, magnesium salts, tetramethylammonium salts, tetraethylammonium salts, tetrabutylammonium salts, methylpyridinium salts, ethylpyridinium salts, methylquinolinium salts, and ethylquinolinium salts of (p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis(p-butylphenyl)boron, and tetrakis(p-butyloxyphenyl)boron (wherein the alkyl group is an n-butyl group, an n-octyl group, an n-dodecyl group, or the like).
[0056] Examples of ascorbic acid compounds include, but are not limited to, L(+)-ascorbic acid, isoascorbic acid, sodium L(+)-ascorbate, potassium L(+)-ascorbate, calcium L(+)-ascorbate, sodium isoascorbate, and the like.
[0057] Examples of thiourea compounds include, but are not limited to, 1,3-dimethylthiourea, tetramethylthiourea, 1,1-diethylthiourea, 1,1,3,3-tetraethylthiourea, 1-allyl-2-thiourea, 1,3-diallylthiourea, 1,3-dibutylthiourea, 1,3-diphenyl-2-thiourea, 1,3-dicyclohexylthiourea, ethylenethiourea, N-methylthiourea, N-phenylthiourea, N-benzoylthiourea, and N-acetylthiourea.
[0058] Examples of vanadium compounds include, but are not limited to, vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, and the like.
[0059] Examples of copper compounds include, but are not limited to, copper acetate, copper salicylate, copper gluconate, copper oleate, copper benzoate, copper acetylacetonate, and copper naphthenate.
[0060] Examples of the organometallic compound include, in addition to the copper compounds, manganese acetylacetone, manganese naphthenate, manganese octoate, cobalt acetylacetone, cobalt naphthenate, lithium acetylacetone, lithium acetate, zinc acetylacetone, zinc naphthenate, nickel acetylacetone, nickel acetate, aluminum acetylacetone, calcium acetylacetone, iron acetylacetone, chromium acetylacetone, and sodium naphthenate, but are not limited to these.
[0061] Examples of organic halogen compounds include, but are not limited to, tetramethylammonium chloride, tetraethylammonium chloride, trioctylmethylammonium chloride, dilauryldimethylammonium chloride, lauryldimethylbenzylammonium chloride, tetra-n-butylammonium chloride, benzyldimethylcetylammonium chloride, and benzyldimethylstearylammonium chloride.
[0062] As the acidic compound to be reacted with aromatic sulfinates, borate compounds, or (thio)barbiturates, any of inorganic acids and organic acids can be used without any limitation, but it is preferable to use organic acids. Furthermore, from the viewpoint of the stability of the cured product, it is most preferable to use organic acids having a polymerizable group, that is, acidic group-containing polymerizable monomers. The acidic group-containing polymerizable monomer is not particularly limited in the type or number of polymerizable groups or acidic groups, and those generally used in the dental field can be used. Examples of acidic groups include carboxyl groups, phosphoric acid groups, phosphonic acid groups, and sulfonic acid groups. Representative acidic group-containing polymerizable monomers used in the dental field include, but are not limited to, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, and 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid. These acidic compounds may be used alone or in combination of two or more.
[0063] Examples of organic boron compounds that react with oxygen or water to initiate polymerization include trialkylborons such as triethylboron, tri(n-propyl)boron, triisopropylboron, tri(n-butyl)boron, tri(s-butyl)boron, triisobutylboron, tripentylboron, trihexylboron, and tricyclohexylboron, as well as partial oxides thereof, but are not limited to these. Examples of organic boron compounds include trialkyl borons such as triethyl boron, tripropyl boron, triisopropyl boron, tributyl boron, tri-sec-butyl boron, triisobutyl boron, tripentyl boron, trihexyl boron, trioctyl boron, tridecyl boron, tridodecyl boron, tricyclopentyl boron, and tricyclohexyl boron; alkoxyalkyl borons such as butoxydibutyl boron; and dialkyl boranes such as butyldicyclohexyl borane, diisoamyl borane, and 9-borabicyclo[3,3,1]nonane. The above compounds may be partially oxidized. Furthermore, these compounds can be used in combination. Among these, tributyl boron or partially oxidized tributyl boron, for example, one in which 0.3 to 0.9 moles of O2 are added to 1 mole of tributyl boron, is preferably used.
[0064] Specific examples of the thermal polymerization initiator that can be suitably used include organic peroxides such as benzoyl peroxide, parachlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, acetyl peroxide, lauroyl peroxide, tertiary butyl peroxide, cumene hydroperoxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dihydroperoxide, methyl ethyl ketone peroxide, and tertiary butyl peroxybenzoate; and azo compounds such as azobisisobutyronitrile, methyl azobisisobutyrate, and azobiscyanovaleric acid, but are not limited to these.
[0065] Examples of the photopolymerization initiator include those made of a photosensitizer, photosensitizer / photopolymerization accelerator, etc. Specific examples of the photosensitizer include α-diketones such as benzil, camphorquinone, α-naphthyl, acetonaphthene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, and naphthoquinone, benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, and 2-methylthioxanthone. Thioxanthones such as thioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; benzophenone, p-chlorobenzophenone, p-methoxybenzophenone, and other benzophenones; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, and other benzophenones; acylphosphine oxides such as bis(2,6-dimethoxybenzoyl)phenylphosphine oxide; α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1; ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, and benzyl (2-methoxyethyl ketal); 3-(4-methoxybenzoyl)coumarin, 3-benzoyl-5,7-dimeth- coumarins such as 3,3'-oxycoumarin, 3,3'-carbonylbis(7-diethylaminocoumarin), and 3,3'-carbonylbis(7-dibutylaminocoumarin); titanocenes such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, and bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium, but are not limited thereto.
[0066] Specific examples of the photopolymerization accelerator include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylanthranilic acid methyl ester, N,N-dihydroxyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl -α-naphthylamine, N,N-dimethyl-β-naphthylamine, triethanolamine, tributylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tertiary amines such as 2,2'-(n-butylimino)diethanol, secondary amines such as N-phenylglycine, barbituric acids such as 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1,3,5-trimethylbarbituric acid, sodium 1,3,5-trimethylbarbiturate, and calcium 1,3,5-trimethylbarbiturate, 2,4,6-tris(trichloromethyl)-s-triazine, 2- Phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,Triazine compounds such as 6-bis(trichloromethyl)-s-triazine, diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis-(4-methylphenyl)iodonium hexafluorophosphate, bis-(4-methylphenyl)iodonium hexafluoroantimonate, bis-(4-methylphenyl)iodonium tetrakis(pentafluorophenyl)borate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, Examples of the dialkyl iodonium salts include diaryliodonium salts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin diversatate, dioctyltin bis(mercaptoacetic acid isooctyl ester) salt, and tin compounds such as tetramethyl-1,3-diacetoxydistannoxane; aldehyde compounds such as lauryl aldehyde and terephthalaldehyde; and sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decanethiol, and thiosalicylic acid, but are not limited to these.
[0067] Furthermore, in order to improve the photopolymerization promoting ability, in addition to the above photopolymerization accelerators, it is effective to add oxycarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxyisobutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, and dimethylolpropionic acid, but the addition is not limited to these.
[0068] These polymerization initiators can be used alone or in combination, regardless of the polymerization mode. Furthermore, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules, if necessary, without any problems.
[0069] The content of the polymerization initiator in the acrylic soft resin composition for denture base of the present invention is not particularly limited, but it is preferable that the content is 0.1% by mass or more and 10.0% by mass or less based on the entire composition. If the content of the polymerization initiator is less than 0.1% by mass, the curing property may be deteriorated and the mechanical properties may be deteriorated. Also, if the content of the polymerization initiator is more than 10.0% by mass, the storage stability may be deteriorated.
[0070] In the acrylic soft resin composition for denture base of the present invention, fillers such as inorganic fillers, hard crosslinked organic polymer particles that do not swell or dissolve in the liquid material, and organic-inorganic composite fillers can be arbitrarily blended for the purpose of adjusting the properties of the powder or liquid material, the properties and curing behavior of the mixture, or the various properties of the obtained cured product, etc. There are no particular limitations on the shape or particle size of these fillers, and the blending amount may be appropriately determined within the range in which flexibility is maintained.
[0071] In addition to the above-mentioned components, the acrylic soft resin composition for denture base of the present invention can contain any of the following components added to the liquid material and / or powder material as necessary: a polymerization inhibitor, a chain transfer agent, an antioxidant, an antibacterial agent, a thickener, a surfactant, a pigment, a dye, an organic fiber, an ultraviolet absorbing agent, and other conventionally known additives.
[0072] In order for the acrylic soft resin composition for denture base of the present invention lined with a denture base to mitigate impact during occlusion, the cured product must exhibit sufficient flexibility. As an index of flexibility, the acrylic soft resin composition for denture base of the present invention has a durometer A hardness of 55 or less after 24 hours and 30 days measured according to the test method described in JIS T 6520:2019 Long-term elastic lining material for denture base, more preferably 45 or less, and even more preferably 35 or less. If the durometer A hardness after 24 hours and 30 days exceeds 55, the impact during occlusion may not be sufficiently mitigated. In addition, in order for the cured product of the acrylic soft resin composition for denture base of the present invention to be used in the oral cavity without discomfort, the difference in durometer A hardness between 24 hours and 30 days is preferably 15 or less, more preferably 5 or less.
[0073] In order for the acrylic soft resin composition for denture base of the present invention to maintain flexibility in the oral cavity for a long period of time, the amount of residual unreacted components in the cured product is preferably 15.0% by mass or less, more preferably 5.0% by mass or less. In this specification, the amount of residual unreacted components means the total of unreacted polymerizable monomers and plasticizers. If the amount of residual unreacted components exceeds 15.0% by mass, the residual unreacted components may gradually dissolve in the oral cavity, causing the cured product to lose flexibility over time. The amount of residual unreacted components can be calculated by dissolving the cured product in an appropriate organic solvent, then centrifuging the solution, adding a poor solvent, filtering, or the like to remove the polymer, and then analyzing the solution after the polymer removal by gas chromatography, high performance liquid chromatography, or the like.
[0074] There are no particular limitations on the powder-liquid ratio in the acrylic soft resin composition for denture base of the present invention, but the mass ratio (powder / liquid) is preferably in the range of 0.4 / 1.0 or more and 2.2 / 1.0 or less, and more preferably in the range of 0.5 / 1.0 or more and 1.6 / 1.0 or less. EXAMPLES
[0075] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. The various components used to prepare the acrylic soft resin compositions for denture bases in the examples and comparative examples, and their abbreviations, are as follows:
[0076] [Monofunctional polymerizable monomer represented by general formula (1)] POB-A: m-phenoxybenzyl acrylate POB-MA: m-phenoxybenzyl methacrylate
[0077] [Monofunctional polymerizable monomers other than the monofunctional polymerizable monomer represented by general formula (1)] MMES: methacryloyloxyethyl methyl succinate PDA: Phenoxydiethylene glycol acrylate PHEMA: Phenoxyethyl methacrylate EMA: Ethyl methacrylate LMA: Lauryl methacrylate
[0078] [Bifunctional or higher polymerizable monomers] 1G: Ethylene glycol dimethacrylate HX: 1,6-hexanediol dimethacrylate
[0079] [Plasticizer] BB: Benzyl benzoate DBS: dibutyl sebacate
[0080] [Organic polymer particles] PEMA: Polyethyl methacrylate particles (50% particle size: 70μm, weight average molecular weight: 650,000, shape: spherical) PEMA2: Polyethyl methacrylate particles (50% particle size: 8μm, weight average molecular weight: 40,000, shape: spherical) PEMA3: Polyethyl methacrylate particles (50% particle size: 110μm, weight average molecular weight: 1.1 million, shape: spherical) PBMA: Polyisobutyl methacrylate particles (50% particle size: 100μm, weight average molecular weight: 400,000, shape: spherical) Copolymer 1: Methyl methacrylate / ethyl methacrylate=50 / 50 copolymer particles (50% particle size: 50μm, weight average molecular weight: 600,000, shape: spherical) Copolymer 2: Ethyl methacrylate / isobutyl methacrylate=50 / 50 copolymer particles (50% particle size: 70μm, weight average molecular weight: 300,000, shape: spherical) Copolymer 3: copolymer particles of methyl methacrylate / ethylene glycol dimethacrylate=99 / 1 (50% particle size: 60μm, weight average molecular weight: -, shape: spherical) Copolymer 4: methyl methacrylate / ethyl methacrylate=60 / 40 copolymer particles (50% particle size: 65μm, weight average molecular weight: 150,000, shape: spherical) Copolymer 5: methyl methacrylate / ethyl methacrylate=40 / 60 copolymer particles (50% particle size: 80μm, weight average molecular weight: 80,000, shape: spherical)
[0081] [Polymerization initiator] BPO: Benzoyl peroxide DMPT: pN,N-dimethyl paratoluidine DEPT: N,N-di(hydroxyethyl)paratoluidine CQ: Camphorquinone DMBE: Ethyl p-dimethylaminobenzoate
[0082] [others] EtOH: Absolute ethanol Elastomer: Cross-linked urethane beads (50% particle size: 6 μm, shape: spherical)
[0083] [Preparation of powder and liquid materials] The various components described above were mixed in the ratios shown in Tables 1 to 3 to prepare powder and liquid materials of the acrylic soft resin composition for denture base used in the examples and comparative examples.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] [Acrylic soft resin composition for denture base] The amount of residual unreacted components and the durometer A hardness after 24 hours and 30 days were measured for acrylic soft resin compositions for denture bases (Examples 1 to 48, Comparative Examples 1 to 7) in which the powder and liquid materials shown in Tables 1 to 3 were combined at the powder-liquid ratios (mass ratios) shown in Tables 4 to 7. The test methods were as follows.
[0088] (1) Amount of remaining unreacted components In an environment of 23±1°C and humidity of 50±10%, the powder and liquid materials of the acrylic soft resin composition for denture base used in the examples and comparative examples were mixed for 20 seconds using a plastic spatula at the powder-liquid ratio (mass ratio) shown in Tables 4 to 7. The mixture was then filled into a stainless steel mold (disk-shaped with an inner diameter of 40 mm and a thickness of 3 mm) and left to stand for 24 hours in an environment of 23±1°C and humidity of 50±10% to harden. The obtained hardened body was immersed in 10 mL of acetone and stirred for 24 hours in an environment of 23±1°C to extract the remaining unreacted components. The amount of the remaining unreacted components in the solution was quantified using high performance liquid chromatography, and it was determined that the amount of the remaining unreacted components was small when the amount of the remaining unreacted components was 15% by mass or less.
[0089] (2) Durometer A hardness According to JIS T 6520:2019 "Long-term elastic lining material for denture base", the durometer A hardness was measured after 24 hours and after 30 days by the following procedure. In an environment of 23±1°C and humidity of 50±10%, the powder and liquid materials of the acrylic soft resin composition for denture base used in the examples and comparative examples were mixed for 20 seconds using a plastic spatula at the powder-liquid ratio (mass ratio) shown in Tables 4 to 7. Next, the mixture was filled into a stainless steel mold (disk-shaped with an inner diameter of 35 mm and a thickness of 6 mm) and left to stand for 30 minutes in an environment of 23±1°C and humidity of 50±10% to harden. The obtained hardened body was immersed in ion-exchanged water and left to stand for 24 hours in a thermostatic chamber at 37±1°C to prepare a test specimen. The durometer A hardness of the test specimen was measured using a durometer A hardness tester (durometer A hardness after 24 hours). The test specimen was then immersed in ion-exchanged water again and allowed to stand in a thermostatic chamber at 37±1°C for 29 days, after which the durometer A hardness was measured (durometer A hardness after 30 days). As a result, when the durometer A hardness after 24 hours and after 30 days was 55 or less, it was determined that the specimen had flexibility. When the difference between the durometer A hardness after 24 hours and the durometer A hardness after 30 days was 15 or less, it was determined that there was little change in flexibility.
[0090] As a result of evaluating these properties, it was determined that the composition having a small amount of residual unreacted components, flexibility, and little change in flexibility had desirable properties as an acrylic soft resin composition for denture base.
[0091] The acrylic soft resin compositions for denture base of the Examples and Comparative Examples were evaluated according to the above-mentioned test methods, and the results are shown in Tables 4 to 7.
[0092] [Table 4]
[0093] [Table 5]
[0094] [Table 6]
[0095] [Table 7]
[0096] [Table 8]
[0097] [Table 9]
[0098] <Example 1> Example 1 had a small amount of residual unreacted components, and had a low Durometer A hardness (after 24 hours) and excellent flexibility. Furthermore, it also showed a low Durometer A hardness (after 30 days), and there was little change in flexibility over time, so it had desirable properties as an acrylic soft resin composition for denture bases.
[0099] <Examples 2 to 48> Examples 2 to 48 are compositions in which the types and amounts of polymerizable monomers, plasticizers, and polymerization initiators, and / or powder-liquid ratios were changed from those of Example 1. As a result of evaluating the compositions of Examples 2 to 48, all of them had low amounts of residual unreacted components, low Durometer A hardness (after 24 hours), and excellent flexibility. Furthermore, they also showed low values for Durometer A hardness (after 30 days), and there was little change in flexibility over time, so they had desirable properties as an acrylic soft resin composition for denture bases.
[0100] <Comparative Example 1> Comparative Example 1 does not contain the monofunctional polymerizable monomer represented by the general formula (1) and contains a large amount of plasticizer. As a result of evaluating Comparative Example 1, it was found that although the Durometer A hardness (after 24 hours) was low and flexibility was excellent, the amount of residual unreacted components was large and flexibility changed significantly over time.
[0101] <Comparative Examples 2 to 4> Comparative Examples 2 to 4 do not contain the monofunctional polymerizable monomer represented by the general formula (1) and contain other monofunctional polymerizable monomers as main components. As a result of evaluating Comparative Examples 2 to 4, the durometer A hardness was at the upper limit of measurement, and it was found that there was no flexibility.
[0102] <Comparative Example 5> Comparative Example 5 does not contain the monofunctional polymerizable monomer represented by the general formula (1) and contains other monofunctional polymerizable monomers as the main component. As a result of evaluating Comparative Example 5, although the durometer A hardness (after 24 hours) was measurable, it was found that the flexibility was poor and the amount of residual unreacted components was relatively large, so that the durometer A hardness (after 30 days) became harder over time.
[0103] <Comparative Examples 6 and 7> Comparative Examples 6 and 7 were mainly composed of elastomer particles or organic polymer particles that did not show solubility or swelling in the liquid material. The cured powder-liquid product did not harden, and various properties could not be evaluated.
[0104] The acrylic soft resin composition for denture base of the present invention can be used to reline dentures that have become ill-fitting due to alveolar ridge absorption to restore the compatibility of the dentures with the oral mucosa and protect the mucosal surface for the long term. [Industrial Applicability]
[0105] The acrylic soft resin composition for denture base of the present invention compensates for the lost viscoelasticity of the alveolar ridge mucosa by lining the mucosal surface of the denture base with a soft material similar to the mucosa, and its cushioning effect reduces the impact during biting, and by distributing pressure evenly over the entire alveolar ridge, it is possible to improve or eliminate pain.
Claims
1. An acrylic soft resin composition for denture bases comprising a liquid material containing a monofunctional polymerizable monomer represented by the following general formula (1) and a powder material containing organic polymer particles that can be swelled or dissolved by the liquid material, wherein at least one of the liquid material and the powder material contains a polymerization initiator. 【Chemistry 1】 (In the formula, R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched divalent hydrocarbon group having 1 to 10 carbon atoms which may contain an ether bond; X 1 represents -O- or -NH-.)
2. The acrylic soft resin composition for denture base according to claim 1, comprising the monofunctional polymerizable monomer represented by the general formula (1) in an amount of 0.5% by mass or more and 70.0% by mass or less based on the entire acrylic soft resin composition for denture base.
3. The acrylic soft resin composition for denture base according to claim 1, comprising the monofunctional polymerizable monomer represented by the general formula (1) in an amount of 5.0% by mass or more and 50.0% by mass or less based on the entire acrylic soft resin composition for denture base.
4. 2. The acrylic soft resin composition for denture base according to claim 1, which has a durometer A hardness of 55 or less after 24 hours.
5. The acrylic soft resin composition for denture base according to claim 1, further comprising a monofunctional polymerizable monomer other than the monofunctional polymerizable monomer represented by the general formula (1) in an amount of 0.5% by mass or more and 45.0% by mass or less based on the entire acrylic soft resin composition for denture base.
6. The acrylic soft resin composition for denture base according to claim 1, further comprising a difunctional or higher polymerizable monomer in an amount of 0.05% by mass to 20.0% by mass based on the entire acrylic soft resin composition for denture base.
7. 2. The acrylic soft resin composition for denture base according to claim 1, further comprising a plasticizer in an amount of 30.0% by mass or less based on the entire acrylic soft resin composition for denture base.
8. 2. The acrylic soft resin composition for denture base according to claim 1, comprising a polymerization initiator in an amount of 0.1% by mass or more and 10.0% by mass or less based on the entire acrylic soft resin composition for denture base.
9. 9. The acrylic soft resin composition for denture base according to claim 1, wherein the amount of remaining unreacted components after curing is 15.0% by mass or less.
Citation Information
Patent Citations
Soft lining material composition for dentistry
JP2002060311A
Soft resin composition for dental tooth plate
JP2002104913A
Soft lining material for dental plate and method of liming dental plate using this lining material
JP2002119523A